EXPRESSION, PURIFICATION, AND ACTIVITY ASSAY OF PEPTIDE SURFACTANT (SupeL00) IN RECOMBINANT ESCHERICHIA COLI - Khairunnisa Wira Rohmat, Riesa
Oil industry these days produce crude oil with only 20%-30% effectiveness through primary and secondary method. It is known that surfactant can form emulsion between water and oil, surfactant may enhance crude oil production up to 200%. However surfactant usually toxic and difficult to be degraded in the natural environment, therefore a biodegradable surfactant is alternative needed. One of the peptide base bio-surfactant is an alternative and designed as reversible biosurfactant. SupeL00 was designed by LEMIGAS. This study aims to produce, purification, and activity assay peptide bio-surfactant SupeL00 that have been constructed into plasmid in previous study. Peptide was produced in recombinant using pET 32b (+) vector. SupeL00 gene have been inserted between Thioredoxin and his-tag with a T7 promoter. After confirmed, plasmid construct was transformed into expression vector E. coli BL21 (DE3), then be expressed by induction of IPTG with 1 mM final concentration. Cell was lysed using sonication lysis buffer and tested for interfacial tension. Protein fusion and SupeL00 threedimensional structure were modeled. Protein fusion Thioredoxin that secreted naturally into periplasmic space, secreted by using Osmotic Shock with 20% . The fusion results that have been secreted out of the cell, then digested using TEV protease at 4°C for 16-18 hours. Fusion proteins that have been separated tested by oil displacement assay and phase behavior assay. Construction SupeL00 gene in this plasmid to produce protein fusion thioredoxin, TEV protease cleavage site, and SupeL00 peptide with total size of ~14 kDa. Interfacial tension measurements showed a unexpected result because lysis buffer using 2% of Triton-X which is a surfactant and modeling results indicate SupeL00 should be separated from the fusion protein in order to function. Osmotic release obtained purer fusion protein which means the fusion proteins successfully secreted out of the cell of E. coli and digestion by TEV protease separate thioredoxin A (~11.8 kDa) and SupeL00 peptide (~2.8 kDa). Oil displacement assay results provide value 2.67 for the separation (SupeL00), the value of 0.27 for thioredoxin as a negative control, and 3.8 for positive control (tween 0.1%) and phase behavior assay shows the differences in surface contact between oil and water. It can be concluded that the SupeL00 peptide has surfactant activities in low intensity.